Weighted pseudo-inverse based control allocation of heterogeneous redundant operating mechanisms for distributed propulsion configuration. (February 2019) - Wang, Zhihui; Zhang, Jing; Yang, Lingyu
Abstract: Distributed propulsion configuration (DPC) usually have heterogeneous redundant operating mechanisms including redundant control surfaces and thrust vector actuators, thus producing strong and complex control coupling between flight and propulsion systems. Then control allocation of heterogeneous redundant actuators is certainly required to realize integrated control. First, the formulation of this specific control allocation problem is given, and then the Moore-Penrose pseudo-inverse method and weighted pseudo-inverse method are introduced to improve control accuracy and coordinate the complex relationship between different types of actuators. Simulation results reveal that the weighted pseudo-inverse method has higher accuracy in allocation result, and it is suitable for the specific control allocation problem for DPC aircraft.